Determinación de las unidades del paisaje en el páramo de la comunidad Aluchan del cantón Pujilí, propuesta de conservación, 2022. - Moya Pazos, Camila Nicole (2023)
The current research project was made directed at the landscape valuation with its specific characterization, the aim is into determining the landscape units state in the Aluchan páramo, located in the La Merced neighborhood, Cusubamba parish, belonging to the Pujilí canton from Cotopaxi province, through the methodologies establishment focused on the landscape units assessment, taking as a reference the following methods: Visual Absorption Capacity (CAV) method, Land Management Bureau (BLM), VRM method, visual sensitivity method, and the visual fragility method, allowing to determine qualitative and quantitative values, what have their specific numbering scales for each component to assess within it, it can we can be mentioned: relief, slope, vegetation, texture, color, erodibility, scenery, spatial configuration. For its compliance, it wasmade a field visit, where it is taken activities evidence, which are carried through in the study area. The got results, the showed, which the BLM values classify it as visual quality very fragile, just like in the CAV results; on the other hand, the calculated values for visual sensitivity vary between class 4 and 5, according pertinent, and for fragility, it determined, what the landscape has a moderate percentage. As a preventive measure, it is required the norms and activities establishment, what ensure good environmental management and thus, to promulgate the natural landscape protection from Aluchan, taking into account the primordial activities for its subsistence.